Student Assignment Policies and Racial and Income Segregation of Schools, School Attendance Zones, and Neighborhoods. (December 2021) - Taylor, Kendra; Frankenberg, Erica
Purpose: This article examines the relationship between educational and residential segregation in three school districts with differing approaches to student assignment. Racial and income segregation within school districts is often only examined at the school level, even as school patterns are often related to residential and attendance zone segregation depending on integration policies aimed at decoupling these relationships.Research Method/Approach: Using an innovative data set, the School Attendance Boundary Survey, along with Census and Common Core of Data data, this analysis examines racial and income segregation at the neighborhood, school zone, and school levels in three districts with varied student assignment policies to explore the relationship between districts' diversity policies and school, attendance zone, and residential segregation.Findings: We find that, despite high residential segregation, educational segregation varies in these three districts. In the two districts that sought to increase diversity in their student assignment policies, educational segregation was lower than in the third district that did not consider diversity, despite similar levels of residential segregation. The findings suggest that district leaders' use of diversity-focused student assignment policies may be one way to disrupt the link between residential and school segregation.Conclusions: Understanding the segregation of educational boundaries within school districts, and the relationship between school zone segregation and segregation at other geographic scales, offers insights into how district leaders could utilize student assignment policies to reduce racial and income segregation.